Bibliometric Analysis of Eco-Friendly Practices in Contemporary Popular Culture - Fatma Sarie; Murthada Murthada; Jusatria Jusatria (West Science Social and Humanities Studies, 2023)
This study undertakes a thorough bibliometric examination of environmentally conscious behaviors in modern popular culture. By applying sophisticated bibliometric techniques and citation analysis, the research reveals important publication patterns, prolific writers, recurring themes, and seminal works in the multidisciplinary domain. The findings show a consistent increase in scholarly output, with significant peaks occurring in tandem with major world events and cultural movements. The discourse's interdisciplinary nature is emphasized by prolific writers and cooperative networks, while thematic clusters including consumer perspectives, green synthesis, and sustainability are revealed through keyword analysis. The ongoing importance of foundational research is highlighted by highly referenced works such as the mainstreaming of green product developments, the idea of planned behavior in green hotels, and the investigation of the Mediterranean diet. In addition to suggesting future options, such as greater consumer insights, breakthroughs in green synthesis, and investigation of sustainable business practices, the research offers cross-cluster insights that highlight the interdependence of topics. In summary, this research provides a sophisticated comprehension of environmentally conscious behaviors in popular culture, providing insightful information to scholars, instructors, and professionals across various disciplines.